Afirmeação de fazeres/saberes : uma proposta de investigação dialogada - Oliveira, Veronica Borges de (2008)
This dissertation presents and discusses the process of research built in the learning relationship with their subjects. It gives visibility to practices of a group of teachers that, with all its limitations and possibilities, feels powerful to build knowledge and to affirm their everyday "to do/to know". Some of these "to do/to know" provided indicators that there is a set, sometimes amorphous and unstructured, but sometimes very organized, of attitudes, knowledge, beliefs, cultures, rules, religiosities, feelings of belonging, and all that, in interaction, "invents" conditions to confront the school learning failure of students. I named this movement "afirmeação of to do/to know" in a reference to the posture of affirmation of a job with the firmness of its convictions, which sometimes are total and others singular, resulting in a contradictory and ambiguous dimension. The theoretical and methodological-epistemological-aesthetic benchmark supports itself in the micro sociology of daily life. The work presents itself with the aesthetics of the medium: multiple entrances and exits. The texts are entitled Intermezzo, with the purpose of emphasizing movement. It expresses discontinuities, cuts, parallels, displacements that emerged in the process of the research. Brings an incarnate discussion, sinking, ambiguous, which gives the tone of the survey: eternal doubts and fragile certainties.